Obstacle Avoidance Path Planning of Planar Redundant Manipulators Using Workspace Density. (11th February 2015) - Dong, Hui; Du, Zhijiang
This paper presents a new approach to generate the workspace of planar redundant manipulators based on the workspace density of a single link. The workspace density of planar serial redundant manipulators can be computed efficiently by using the concept of the Fourier transform for the group of rigid-body motions of the plane and the convolution theorem. For manipulators using discrete actuation, it is important to study not only the shape of the workspace, but also the density of reachable poses in the workspace. In this paper, we focus on using the workspace density to calculate collision-free paths in complex environments with multiple obstacles in the workspace of the manipulator. This paper presents the algorithm and demonstrates it effectiveness using simulation results.